2020
DOI: 10.3390/ijerph17114049
|View full text |Cite
|
Sign up to set email alerts
|

How Much Is the Eco-Efficiency of Agricultural Production in West China? Evidence from the Village Level Data

Abstract: This study evaluates the eco-efficiency of agriculture in Pupiao Town, in the Yunnan province of China, through micro-level research. The term "eco-efficiency" refers to the efficiency with which ecological resources are used to meet human needs. Interviews and field research were conducted to collect the data of the 23 villages from 2016 to 2018. The Data Envelopment Analysis model (DEA) was used for data analysis. The results were as follows: (1) The eco-efficiency scores of Pupiao Town had considerable spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Such studies include domestic water buffaloes: Access to surface water, disease prevalence and associated economic losses (Elahi et al, 2018), The public policy of agricultural land allotment to agrarians and its impact on crop productivity in Punjab province of Pakistan (Elahi et al, 2019), How Much Is the Eco-Efficiency of Agricultural Production in West China? Evidence from the Village Level Data (Xiang et al, 2020), Determinants of the involvement of extension agents in disseminating climate smart agricultural initiatives: Implication for scaling up (Olorunfemi et al, 2019), Climate Change Adaptation in the Delta Nile Region of Egypt: Implications for Agricultural Extension (Kassem et al, 2019…”
Section: Review Articlementioning
confidence: 99%
“…Such studies include domestic water buffaloes: Access to surface water, disease prevalence and associated economic losses (Elahi et al, 2018), The public policy of agricultural land allotment to agrarians and its impact on crop productivity in Punjab province of Pakistan (Elahi et al, 2019), How Much Is the Eco-Efficiency of Agricultural Production in West China? Evidence from the Village Level Data (Xiang et al, 2020), Determinants of the involvement of extension agents in disseminating climate smart agricultural initiatives: Implication for scaling up (Olorunfemi et al, 2019), Climate Change Adaptation in the Delta Nile Region of Egypt: Implications for Agricultural Extension (Kassem et al, 2019…”
Section: Review Articlementioning
confidence: 99%
“…It is reported that pest and disease outbreak can decrease crop yield by 40%. 15 Conversely, appropriate application of agrochemicals can increase crop yields significantly, 29 , 30 a return that encourages more farmers to use agrochemicals. However, the question remains to what extent agrochemical uses impact the environment and humans, and whether the gain in yield outweighs the health and environmental damage.…”
Section: Introductionmentioning
confidence: 99%
“…The main carbon sources for agriculture production activities were identified as chemical fertilizer, pesticide, film, diesel, irrigation, and tillage. Based on existing studies [4,20,46], the values used for the emission coefficients are as follows: agricultural chemical fertilizer (0.8956 (t/t)), agricultural pesticide (4.9341 (t/t)), agricultural film (5.18(t/t)), agricultural diesel (0.5927 (t/t)), agricultural irrigation (0.26648 (t/hm2), and arable land (0.3126 (t/hm2)).The agricultural expected output indicators were characterized using the total agricultural output value.…”
Section: Agriculture Carbon Emission Was Incorporated As Undesirable Agriculturalmentioning
confidence: 99%
“…Increasing agricultural eco-efficiency would mean improving farm product quality (food safety and issue), lowering carbon emission, and enhancing resource utilization [16]. Agriculture eco-efficiency has been applied at various scales, from the national level [1,17], provincial level [18], city level [19], village level [20], up to the farm level [21,22]. However, based on our review of previous studies, little research has been conducted evaluating agricultural eco-efficiency at the county level, particularly in Jiangsu province.…”
Section: Introductionmentioning
confidence: 99%